Evaluating System Buckling Load of a Plane Non-sway Frame by Hand - Li, Kuinian (European Journal of Applied Sciences, 2022)
Presented in this paper is a simple method for system buckling analysis of plane non-sway frames. The “bracing” of a non-sway frame is first released and becomes a sway frame named accompanying sway frame. The upper-bound of the system buckling load of the accompanying sway frame can be found by a story buckling method developed. From the comparison study of a single sway column and a non-sway column, a modification factor can be obtained. The upper-bound of the system buckling load of the non-sway frame can be determined by the upper-bound of the system buckling load of its accompanying sway frame, multiplied with this modification factor. The upper-bound of system buckling load is the buckling load when the rigidity of the beams connected to the columns can be considered infinite. The system buckling load can be evaluated from the upper-bound, modified by real parameters of the frame with the design graphs developed. Examples are presented and the procedures are demonstrated. The system buckling load produced by the suggested approach is compared with that produced by system buckling analysis with FEA. The accuracy, efficiency and simplicity of the suggested system buckling approach are demonstrated.